Como fazer santas e sereias: imaginária de umbanda, design e sociedade - ANDRADE, Renan Vieira (2017)
The religious images used by Umbanda, a Brazilian religion characterized by the presence of elements of indigenous, African and European cultures, are generally represented by semi-industrial three- bimensionaI reprobgctions in pIaster. AIthoggh we finb in the imagery of umbanda representations of idealized types of national identity, adoptions and adaptations of foreign iconographic models are evident. Understanding these images as a material culture, this dissertation proposes an analysis of this iconography considering its sociaI contexts anb the inflgence of besign, throggh images of mass consumption, in the construction of its particular imaginary.